Combined Operation of a New Power Angle Control Unit Vector Template Based Unified Power Quality Conditioner and Fuel Cell Stack Supply with Effective Utilization of Shunt and Series Inverter. Issue 18 (7th November 2016) - Panda, Anup Kumar; Patnaik, Nishant
Abstract: This article presents a new power angle control unit vector template based simplified approach for controlling a unified power quality conditioner for a single-phase distribution system along with a boost converter based fuel cell stack source supplying to the load via both shunt and series inverters under voltage interruption condition, thus reducing the burden on the shunt inverter. The power angle control concept is embedded with a unit vector template method for efficient utilization of both inverters of the unified power quality conditioner, namely shunt and series. Each of the major power quality disturbing elements in a single-phase distribution system, such as harmonic distortions in current and voltage, voltage sag and swell, reactive power demand, and voltage interruption, is properly handled along with an ease of implementation. A fuel cell stack combined with a boost converter is used as an independent external source during voltage interruption for maintaining the supply chain to the load through both available inverters, thus reducing the burden and effective rating of the shunt inverter. The entire system is implemented using MATLAB/SIMULINK (The Math Works, Natick, MA) and is also implemented with RT-LAB (OPAL-RT Technologies, Montreal, QC, Canada) for real time simulative analysis.